To find the equation of \( g(x) \) that represents the reflection of \( f(x) \) across the x-axis, we start with the equation of \( f(x) \):
\[ f(x) = |x| + 2 \]
When reflecting a function across the x-axis, we negate the entire function. This means that for \( g(x) \), we will change the sign of \( f(x) \):
\[ g(x) = -f(x) \]
Now, substituting \( f(x) \) into this equation:
\[ g(x) = -(|x| + 2) \]
Distributing the negative sign:
\[ g(x) = -|x| - 2 \]
So the final form of the equation for \( g(x) \) is:
\[ g(x) = -|x| - 2 \]
Therefore, you can fill in the blanks as follows:
\[ g(x) = -|x| - 2 \]